Willingness of human immunodeficiency virus‐positive patients to donate their organs for transplantation in Taiwan: a cross‐sectional questionnaire survey. Issue 6 (11th November 2016) - Lee, Yi‐Chieh; Hung, Chien‐Ching; Cheng, Aristine; Liu, Wen‐Chun; Wu, Pei‐Ying; Yang, Shang‐Ping; Zhang, Jun‐Yu; Luo, Yu‐Zhen; Chang, Hsi‐Yen; Sun, Hsin‐Yun; Chang, Shan‐Chwen
Abstract: Background: With the introduction of combination antiretroviral therapy (cART) that has significantly improved survival, human immunodeficiency virus (HIV)‐positive patients may be potential organ donors to HIV‐positive recipients in a few countries. Organ shortage remains a challenge for organ transplantation in Taiwan, where organ donation by HIV‐positive patients remains prohibited by law. Methods: We assessed the willingness of organ donation (should they be pronounced brain dead, and the ban on HIV‐positive organ donation be lifted) among HIV‐positive patients who received regular HIV care at a university hospital in a cross‐sectional survey between May and August 2015 with the use of an anonymous, self‐administered questionnaire interview. Results: Of the 1010 participants, 93.7% were receiving cART with the latest mean CD4 count and plasma HIV RNA load of 587 cells/mm 3 and 2.73 log10 copies/mL, respectively. Overall, 71.9% were willing to donate organs. In multivariate analysis, factors associated with willingness to donate organs included college or graduate school diploma (odds ratio [OR] 1.571, 95% confidence interval [CI] 1.166‐2.191), registered willingness to donate in the National Health Insurance system (OR 9.430, 95% CI 1.269‐70.051), and knowledge of the information on HIV‐positive deceased donors (HIVDD) (OR 1.673, 95% CI 1.073‐2.608). Conclusions: We concluded that a significant proportion (71.9%) of HIV‐positive Taiwanese patients were willing to donate their organs. The willingness was associated with a higher education level, prior registered willingness to donate organs, and awareness of HIVDD.